2003
DOI: 10.1046/j.1469-8137.2003.00761.x
|View full text |Cite
|
Sign up to set email alerts
|

Rust haustoria: nutrient uptake and beyond

Abstract: SummaryHaustoria are morphological features of an extremely successful class of plant parasites, the obligate biotrophs. The broad phylogenetic spectrum of organisms producing haustoria suggests that these structures have arisen many times in the course of evolution and represent specific adaptations of these organisms to the close interaction with their respective host plants. This close interaction and the fact that these structures cannot be produced in vitro have hampered an analysis of the roles of hausto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
182
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(192 citation statements)
references
References 60 publications
9
182
0
1
Order By: Relevance
“…6A), the global functional distribution of proteins in conidia and the sporulating hyphae was very similar, whereas the haustorial proteome showed intriguing differences. The over-representation of carbohydrate metabolism in general and monosaccharide metabolism in particular was not surprising given our understanding that haustoria are the primary feeding structures (25) and that monosaccharides are thought to be the main form of fixed carbon taken up by the fungus (26). This also correlates well with our previous findings based on analysis of transcriptome dynamics where we have shown that genes encoding glycolytic enzymes are coordinately up-regulated in haustoria (8).…”
Section: Discussionsupporting
confidence: 87%
“…6A), the global functional distribution of proteins in conidia and the sporulating hyphae was very similar, whereas the haustorial proteome showed intriguing differences. The over-representation of carbohydrate metabolism in general and monosaccharide metabolism in particular was not surprising given our understanding that haustoria are the primary feeding structures (25) and that monosaccharides are thought to be the main form of fixed carbon taken up by the fungus (26). This also correlates well with our previous findings based on analysis of transcriptome dynamics where we have shown that genes encoding glycolytic enzymes are coordinately up-regulated in haustoria (8).…”
Section: Discussionsupporting
confidence: 87%
“…The following properties appear to be hallmarks of these fungi: (i) highly developed infection structures; (ii) limited secretory activity, especially of lytic enzymes; (iii) carbohydrate-rich and protein-containing interfacial layers that separate fungal and plant plasma membranes; (iv) haustoria, which are specialized hyphae for nutrient absorption and metabolism; (v) both long-term suppression of host defences and induction of specific host genes for the establishment of biotrophy (Mendgen and Hahn, 2002;Shulze-Lefert and Panstruga, 2003;Voegele and Mendgen, 2003).…”
Section: Fungal Infection Processmentioning
confidence: 99%
“…One of the primary functions of haustoria seems to be to facilitate nutrient uptake from the host (Hahn and Mendgen, 2001). Haustoria formation also induces structural changes in the host cell, including cytoskeletal rearrangements, nuclear migration, and chromatin condensation (Kobayashi et al, 1994;Heath, 1997), and there is some evidence that compatible rusts can suppress host defense responses and influence host cell metabolism (Mellersh and Heath, 2001;Ayliffe et al, 2002;Voegele and Mendgen, 2003). However, the signals leading to these changes are not known.…”
Section: Introductionmentioning
confidence: 99%